Development and Validation of Factors Affecting Telenutrition Adoption among Malaysian Dietitians Questionnaire - Mohd Daud, Nur Liyana Hasnaa; Mohamed Nor, Noraishah; Jaafar, Nurul Hazirah; Abu Bakar, Wan Azdie Mohd Abu Bakar; Mohd Shukri, Nor Azwani (Jurnal Gizi dan Pangan, 2025)
This study aimed to determine the validity of a newly developed questionnaire to assess dietitians' understanding of the factors influencing telenutrition adoption in Malaysia. As such, a questionnaire was developed to assess dietitians’ professional changes, acceptability, barriers, and facilitators to telenutrition implementation. It was constructed based on published questionnaires and an extensive literature review. The questionnaire comprising 52 items, underwent content and face validity assessments. Eight dietetics experts with academic and clinical backgrounds and more than five years of experience in the field evaluated the questionnaire items for relevance, clarity, simplicity, ambiguity, readability, and practicality. The experts quantitatively assessed the questionnaire using a Likert scale rating and additional comments. The Content Validity Index (CVI) was determined using item and scale indices (I-CVI/S-CVI/Ave). The findings show that the I-CVI score ranged between 0.78 and 1.00, and the S-CVI/Ave was >0.87. Thirteen items with an I-CVI score of <0.83 were deleted. Based on the feedback, revisions were made to the instructions and questions regarding clarity, redundancy, ambiguity, or item length. Then, face validation was qualitatively conducted by cognitive review (n=7). This utilized think-aloud and verbal-probing techniques on participants with experience providing telenutrition services for >2 years. The interview was transcribed verbatim and analyzed using ATLAS.ti software. Twelve items were amended due to ambiguity and unclear meanings. The final questionnaire with thirty-nine items is valid to assess the factors influencing telenutrition adoption among Malaysian dietitians.